2009
DOI: 10.3174/ajnr.a1839
|View full text |Cite
|
Sign up to set email alerts
|

Diffusely Abnormal White Matter in Progressive Multiple Sclerosis: In Vivo Quantitative MR Imaging Characterization and Comparison between Disease Types

Abstract: BACKGROUND AND PURPOSE:Recent postmortem studies in MS brain suggest that the severity of changes in DAWM can be measured by using quantitative MR imaging. This study aimed to characterize DAWM in vivo by using 4 quantitative MR imaging measures and to explore differences between MS disease types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 27 publications
5
54
0
Order By: Relevance
“…This is consistent with previous findings where Vrenken et al (158) showed that DAWM was an intermediary in T1 . This may reflect the relative increase of the extracellular water of the tissues, where focal lesions have the highest increase, DAWM has a less pronounced increase, and NAWM only has a slight increase.…”
Section: Diffusely Abnormal White Mattersupporting
confidence: 83%
See 3 more Smart Citations
“…This is consistent with previous findings where Vrenken et al (158) showed that DAWM was an intermediary in T1 . This may reflect the relative increase of the extracellular water of the tissues, where focal lesions have the highest increase, DAWM has a less pronounced increase, and NAWM only has a slight increase.…”
Section: Diffusely Abnormal White Mattersupporting
confidence: 83%
“…Recent studies, however, suggest that these changes may be important markers of disease progression (157,158). Technological developments have therefore been suggested to characterise and quantify DAWM, as well as to detect changes in NAWM.…”
Section: Diffusely Abnormal White Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…24 Our findings that children with acute demyelinating syndromes consistent with either monofocal CIS, polyfocal CIS with encephalopathy, or polyfocal CIS without encephalopathy did not demonstrate significant anisotropic abnormalities in the NAWM suggest that these diffuse pathologic processes are not present acutely at the time of clinical disease onset. Our definition of NAWM excluded overt focal lesions but included dirty-appearing white matter, 25 and further studies are required to dissociate these entities in pediatric MS. Similar to our work, a recent study found significantly decreased mean FA in the NAWM callosal fibers and NAWM corticospinal tracts and significantly increased MD in the NAWM corticospinal tracts in adult MS compared with the pediatric MS/CIS and adult CIS groups.…”
Section: Discussionmentioning
confidence: 99%